2020
DOI: 10.1186/s13006-020-00258-z
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone support to sustain exclusive breastfeeding in the community after hospital delivery and counseling: a quasi-experimental study

Abstract: Background: Rapid increases in hospital and cesarean deliveries threaten an already falling exclusive breastfeeding rate (EBR) in Bangladesh. There is neither a sustained Baby-Friendly Hospital Initiative (BFHI) nor any community support for breastfeeding mothers. Our aim was to find out whether breastfeeding support after hospital delivery and subsequently by mobile phone at home is effective in improving EBR in infants under six-months of age. Methods: A quasi-experimental study was carried out in 2010 at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
1
14
1
1
Order By: Relevance
“…In a two armed, prospective study of pregnant women through the post-partum phase, Patel and team [ 24 ] showed that women who used mobile phones were 6 times more likely to exclusively breastfeed than than those in the control arm (AOR [95% CI]: 6.3 [4.9–8.0]). Similar results were reported by Jerin et al, [ 25 ] in a population of Bangladeshi women. Additional clinical trials of mothers in Nigeria, China, and Kenya [ 9 ] also support the finding that SMS/cell phone interventions improve EBF rates up to 4 months post-partum.…”
Section: Discussionsupporting
confidence: 91%
“…In a two armed, prospective study of pregnant women through the post-partum phase, Patel and team [ 24 ] showed that women who used mobile phones were 6 times more likely to exclusively breastfeed than than those in the control arm (AOR [95% CI]: 6.3 [4.9–8.0]). Similar results were reported by Jerin et al, [ 25 ] in a population of Bangladeshi women. Additional clinical trials of mothers in Nigeria, China, and Kenya [ 9 ] also support the finding that SMS/cell phone interventions improve EBF rates up to 4 months post-partum.…”
Section: Discussionsupporting
confidence: 91%
“…It may be difficult to improve EBF practices among poor women who lack formal education, particularly when the majority of births take place in homes and are assisted by skilled/traditional birth attendants (TBA) in Bangladesh [ 50 ]. Nonetheless, social and behavioral change interventions [ 68 ], such as maternal counselling [ 69 ], mobile phone follow-up services [ 70 ], and training TBAs [ 71 ] to improve breastfeeding practices for home births in Bangladesh may be effective. Furthermore, a recent study reported a number of interventions such as education and counselling, maternal and newborn health initiatives, community mobilization, and mass media, delivered across several implementation environments- health facility, community, and home/family, were effective in improving breastfeeding practices including early initiation of breastfeeding and EBF in various South Asian countries [ 72 ].In LMICs, wealthier and educated mothers are also more likely to deliver through a caesarean section as compared to vaginal delivery [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that extend healthcare and interpersonal support beyond health facilities have also shown promise in South Africa and other LMICs [19,40,41]. MomConnect is one component of a national strategy to increase EBF rates and support new mothers.…”
Section: Healthcare Influencesmentioning
confidence: 99%